Quantifying Annual Nitrogen Loss to Groundwater Via Edge‐of‐Field Monitoring: Method and Application. Issue 1 (23rd June 2022) - Cardiff, Michael; Schachter, Laura; Krause, Jake; Gotkowitz, Madeline; Austin, Brian
Abstract: Increased nitrate concentrations in groundwater and surface waters represent one of the most widespread and acute impacts of modern agriculture on the environment. However, there is often a fundamental gap in understanding how individual agricultural fields and practices contribute to this broad‐scale issue. To practically address nutrient dynamics at individual agricultural sites, methods for assessing nitrogen loss to groundwater that are minimally invasive and thus can encourage farmer "buy in" are necessary. We present an approach that uses edge‐of‐field monitoring at multilevel samplers along with a once‐per‐year tracer application (bromide) to calculate nitrogen loss on an annual basis. Using appropriate spatio‐temporal integrals of measured concentrations, a net loss of nitrogen to groundwater (per field area) can be calculated. This approach directly measures impacts of nitrogen leaching below the water table, while avoiding permanent in‐field installations that can interfere with farm operations. We present an application of this technique to assess nitrogen loss to groundwater over 5 years for a commercial agricultural field in Sauk County, WI. Results from Field 19 indicate that nitrogen losses are similar to (or slightly below) previously reported values for corn and potato crops. In all years, however, we estimate that more than 25% (>60 kg/ha) of nitrogen applied leached as nitrate to groundwater. Use of this mass flux estimation method was most reliable when: (1) tracer is injected directly at the water table, limiting "smearing" within the vadose zone; and (2) nitrate concentrations from laboratory analysis were obtained, rather than using ion‐selective electrodes or nitrate test strips. Abstract : Article Impact Statement : We demonstrate a minimally invasive monitoring approach that quantifies nitrogen loss to groundwater from an agricultural field over five growing seasons.